Sharia-Based Legal Formula For Personal Data Protection In The Financial Services Industry Post-Covid-19 Pandemic - Deny Susanto (BULLET : Jurnal Multidisiplin Ilmu, 2022)
As a country with a substantial Muslim population, Indonesia provides a market for sharia-based financial firms. Corporate organizations, minimal liability companies, seek the most effective way to promote business growth. One objective is to develop its digital ecosystem for the financial services industry, including banking, insurance, capital markets, and non-bank financing organizations. The most crucial factor is the corporation's attempts to deliver effective and efficient services in response to the community's demands as the number of Covid-19 cases continues to fall and the economy begins to improve. This study aims to examine the perspectives on formulating the right and applicable law for the protection of personal data in the management conducted by corporations in the sharia-based financial services sector in Indonesia during the Covid-19 pandemic as post-pandemic expectations. Covid-19 examines law enforcement for potential personal data violations on technology users by businesses. Finding an appropriate and effective legal formulation that can be fundamentally applied in the form of fair regulations and in accordance with sharia values in parallel is the result of the research, and it can be concluded that the formulation of legal rules can rapidly provide regulatory solutions to achieve an equilibrium of rights. and justice for businesses based on sharia law.